THE RELATION BETWEEN THE CYCLE OF ADMINISTRATION OF CHEMOTHERAPY TO PSYCHOSOCIAL PROBLEMS IN BREAST CANCER PATIENTS (STIKes Mitra Keluarga, 2021)
Introduction: Breast cancer is the most common malignant neoplasm that affects women. One of the treatments for breast cancer is chemotherapy which is carried out according to a particular schedule with a specified length of therapy to increase the patient's recovery rate. In addition to the physiological effects, chemotherapy also has a psychological impact on the patient. Fulfillment of psychosocial needs is important to improve the quality of life of patients caused by changes in physical, social, cognitive, spiritual, emotional and role functions. The purpose of this study was to determine the relationship between the cycle of chemoteraphy with psychosocial problems in breast cancer patients. Method: This study is a quantitative correlational study using 54 breast cancer patients as samples by purposive sampling. Data collection was carried out during April 2020 to June 2020 in the chemotherapy room at Koja Hospital, North Jakarta. The Depression Anxiety Stress Scale (DASS 21) questionnaire was used to identify psychosocial problems in breast cancer patients. Statistical analysis of the Spearman rank test was carried out to analyze the relationship between chemotherapy cycles and psychosocial problems. Results: The results showed that there was a relationship between chemotherapy cycles and psychosocial problems (p value 0.001) although it showed a weak relationship between those two variables (r 0.257). Psychosocial problems identified included anxiety (53%), depression (9.3%), low self-esteem (16.7%) and stress (20.4%). Conclusion: Nurses need to provide comprehensive nursing care for patients undergoing chemotherapy including identifying problems related to physical complaints and psychosocial needs so that nursing interventions can be given comprehensively to breast cancer patients undergoing chemotherapy.